Ordklassepotentiale - Jensen, Eva Skafte (Ny forskning i grammatik, 2016)
In this paper, the issue of lexical categories is discussed. Traditionally, words are considered to belong to lexical categories, and if they are used in ways known to be the properties of other categories, this use is considered derived or secondary. In this paper, it is proposed that words do not belong to a lexical category before they are used, but that they instead hold the potential to belong to one or more categories. The assignment of lexical category only takes place in specific morphosyntactic contexts. Thus, according to the idea of potential, a word like hjem ‘home’ is not a noun a priori, but holds the potential of being a noun et smukt hjem ‘a beautiful home’ or an adverb jeg skal hjem ‘I must-go home’ in the proper contexts.